2011
DOI: 10.1080/00949650903418883
|View full text |Cite
|
Sign up to set email alerts
|

New acceptance sampling plans based on life tests for Birnbaum–Saunders distributions

Abstract: In this paper, we consider the Birnbaum-Saunders distribution as a life model to develop various acceptance sampling schemes based on the truncated life tests. We develop the double sampling plan and determine the design parameters satisfying both the producer's and consumer's risks simultaneously for the specified reliability levels in terms of the mean ratio to the specified life. We also propose a group sampling plan and determine the parameters by the above-mentioned two-point method. Tables are constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…( 1 1 ) As suggested by Aslam et al, [18] it more convenient for life test to write t 0 as t 0 = aθ 0 for a constant termination ratio a. Therefore, Equation (11) can be rewritten as…”
Section: Mdsp Under the Weibull Distributionmentioning
confidence: 97%
“…( 1 1 ) As suggested by Aslam et al, [18] it more convenient for life test to write t 0 as t 0 = aθ 0 for a constant termination ratio a. Therefore, Equation (11) can be rewritten as…”
Section: Mdsp Under the Weibull Distributionmentioning
confidence: 97%
“…Some generalizations and extensions of the BS distribution are presented in Díaz-García and Leiva (2005), Gómes et al (2009), Guiraud et al (2009) and Cordeiro and Lemonte (2011. Bhatti (2010) introduced the BS autoregressive conditional duration model and Aslam et al (2011) developed various acceptance sampling schemes based on the truncated life tests. This distribution has been applied in reliability studies (Balakrishnan et al 2007) and outside this field (Leiva et al 2008).…”
mentioning
confidence: 99%
“…A generalization of the single acceptance sampling plan is known as the double acceptance sampling plan. Such plans have also found wide applications in the area of quality control and reliability analysis and one may refer to Aslam and Jun (2010) and Aslam et al (2011a) for some related results. Balasooriya (1995) suggested that when the test units are highly reliable but relatively cheap and the test facilities are scarce, a life test experiment can be conducted by placing g independent groups on the test where each group contains r number of units.…”
Section: Introductionmentioning
confidence: 99%
“…Note that g, r and c are the design parameters of the associated group acceptance sampling plan. In literature, group acceptance sampling plans have been discussed by Aslam et al (2009) for gamma distribution, Aslam and Jun (2009a) for Weibull distribution, Aslam and Jun (2009b) for inverse Rayleigh and log-logistic distributions, Rao (2010) for generalized exponential distribution and Aslam et al (2011a) for Birnbaum-Saunders distribution. It is to be noticed that two-stage group acceptance sampling plan is a further generalization of the group acceptance sampling plan.…”
Section: Introductionmentioning
confidence: 99%